Real-time observation of X-ray-induced intramolecular and interatomic electronic decay in CH2I2 - Fukuzawa, Hironobu; Ghosh, Aryya; Gokhberg, Kirill; Cederbaum, Lorenz S.; Kuleff, Alexander I. (Nature Communications, 2019)
Understanding strong X-ray induced phenomena is important for applications of X-ray free-electron laser imaging. Here, the authors show time-resolved measurements of X-ray free-electron laser induced electronic decay of CH2I2 molecule probed with NIR pulses and identify mechanisms behind different transient states lifetimes.
Die Ziffer "2" ist im Titel jeweils tiefgestellt
Gesehen am 26.06.2019